Hubungan Antara Kesadaran Metakognitif dengan Keterampilan Proses Sains bagi Peserta Didik pada Pembelajaran Fisika - Bela Bela; Andika Kusuma Wijaya; Haris Rosdianto (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This study aims to: 1) describe the metacognitive awareness profile of students in physics learning, 2) describe the science process skills profile of students in physics learning, and 3) analyze the relationship between metacognitive awareness and students' science process skills in physics learning. This research used a quantitative approach with descriptive data analysis techniques and a causal research design. The population of the study consisted of 120 students from SMP Negeri 20 Singkawang, with a sample selected using saturated sampling techniques. Data collection was performed using two instruments: the Metacognitive Awareness Inventory (MAI), which includes 45 statements, and a science process skills test consisting of 14 multiple-choice questions designed to evaluate core cognitive competencies. The findings of the study indicated that: 1) the metacognitive awareness of students in grades VIIIA, VIIIB, VIIIC, and VIIID was categorized as high, 2) the science process skills of students in grades VIIIA, VIIIB, VIIIC, and VIIID were also categorized as high based on overall performance metrics, and 3) there was no significant relationship between metacognitive awareness and students' science process skills. Based on these results, the hypothesis test concluded that there is no significant relationship between metacognitive awareness and science process skills, suggesting that the correlation between the two variables is low. This study contributes to understanding the profiles of metacognitive awareness and science process skills in physics learning, as well as their lack of correlation, which can serve as a basis for further research and the development of innovative strategies to improve both aspects in future physics education.